How do human rights violations affect poverty and income distribution? - Nikolaos Apergis; Arusha Cooray (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
The goal of this paper is to examine the impact of human rights on income distribution and poverty by exploring how both aid and trade can influence poverty and income distribution through human rights. The analysis employs data for 125 countries and uses a number of panel data methods. The results suggest that stronger human rights contribute to greater income equality and poverty reduction. The interaction of human rights with official development assistance and trade flows shows that as they increase, or, alternatively, as human rights records increase, both official development assistance and trade flows reduce poverty and lead to greater income equality. The region-disaggregated results suggest that promoting better human rights records is important for poverty alleviation and contributing to greater equality in income distribution.
Keywords: D63; I32; K38; O57; C33; 330; global panel of countries; human rights; income inequality; poverty